Microbial contamination of open‐but‐unused portions of wound dressings stored in home settings. Issue 1 (19th October 2017) - Templeton, Sue; Wong, Ching; Rando, Tabatha; Adamson, Penny; Lynn, Penny
Abstract: The purpose of this study was to investigate incidence rates and levels of microbial contamination in open‐but‐unused portions of wound dressings stored in home settings. Portions of wound dressings were collected at up to four home visits for 104 clients undertaking wound management within their home. A control sample and stored sample was collected on each home visit and sent for pathology testing to identify levels of microbial contamination. The stored open‐but‐unused wound dressings were managed according to a written protocol. Of the tested samples ( n = 776), 6% of control samples and 7% of test samples had microbial contamination. From regression analysis, the stored samples were more likely to have microbial contamination than control samples, but results were not statistically significant. In comparing occasions of storage and handling across four home visits, after adjusting for sample group and dressing type, none of the home visit occasion regressions were statistically significant. In conclusion, storage of open‐but‐unused portions of wound dressings kept in home settings does not appear to increase the rate of microbial contamination compared to newly opened wound dressings.